MOLECULAR STRUCTURE, VIBRATIONAL SPECTRA AND IN SILICO EVALUATION OF TRIFLUSULFURON-METHYL (International Journal of Food and Nutritional Sciences, 2022)
Density functional theory calculations have been performed with B3LYPfunctional and 6-311+G(d,p) basis set implemented in the Gaussian 09 package inorder tosupport spectral characteristics and geometry of triflusulfuron-methyl, a molecule known for itsherbicidal activity. The observed Raman and infrared spectral bands have been assigned in theframework of theoretical frequencies and intensities. Aromaticity of the phenyl and triazine ringshas been measured based on harmonic oscillator model of aromaticity index. Natural bondorbital analysis performed on triflusulfuron-methyl has been carried out to reveal various nonbondinginteractions present in the molecule. Triflusulfuron-methyl has been tested for itsantimicrobial activity and found to exhibit antifungal and antibacterial effects.